Dual targeting of EZH1 and EZH2 for the treatment of malignant rhabdoid tumors - Haruka Shinohara; Rie Sawado; Makoto Nakagawa; Ayuna Hattori; Kazutsune Yamagata; Kimiharu Tauchi; Jumpei Ito; Yasumichi Kuwahara; Tsukasa Okuda; Chitose Ogawa; Issay Kitabayashi (Molecular Therapy: Oncolytics, 2022)
Malignant rhabdoid tumors (MRTs) are rare and highly aggressive pediatric cancers with no standard of care. MRTs are characterized by loss of SMARCB1, which results in upregulated expression of enhancer of zeste homolog 2 (EZH2), which is responsible for the methylation of lysine 27 of histone H3 (H3K27me3), leading to the repression of gene expression. Although previous reports suggest EZH2 as an effective therapeutic target, the functions of EZH1, the other homolog of EZH, in MRT remain unknown. Here, we show that EZH1, as well as EZH2, contributes to MRT cell growth and H3K27 methylation. Depletion or selective inhibition of EZH2 led to a compensatory increase in EZH1 expression, and depletion of EZH1 enhanced the effect of EZH2 inhibition. EZH1/2 dual inhibitors suppressed MRT cell growth markedly, reflecting the reduction of H3K27me3 accumulation at one of the EZH1/2 targets, the CDKN2A locus. Dual inhibition of EZH1/2 in vivo suppressed tumor growth completely, with no significant adverse effects. These findings indicate that both EZH1 and EZH2 are potential targets for MRT therapy, and that EZH1/2 dual inhibitors may be promising therapeutic strategies for MRT.